Makna Teologis Memberi Persembahan Perpuluhan Dalam Perjanjian Lama: Theological Meaning of Giving Tithe Offerings in the Old Testament - Citra Pangalinan Situmorang; Metalia Margaret; Bobby Kurnia Putrawan (MODERATE: Journal of Religious, Education, and Social, 2023)
Tithing is a practice that has long been debated among Christians, especially regarding its relevance and theological meaning in the Old Testament. Many Christians give tithes without fully understanding the biblical foundation and spiritual significance behind it. This study aims to explore the theological meaning of tithing in the Old Testament and its implications for Christian life today. The research uses a qualitative literature review method, analyzing biblical texts (Genesis, Leviticus, Numbers, Deuteronomy, Malachi) and relevant scholarly works on tithing. The results reveal four main theological meanings: (1) tithing as an expression of gratitude for what one possesses; (2) withholding tithes as an act of rebellion against God; (3) tithing as an acknowledgment of God’s sovereignty over all possessions; and (4) tithing as having eternal value, rooted in faith, covenant, and compassion for the poor. The study concludes that tithing is not merely a legal obligation but a spiritual discipline that reflects a believer’s relationship with God and commitment to social justice. Contribution: This study contributes a comprehensive theological framework of tithing in the Old Testament, clarifying its fourfold meaning and demonstrating that tithing is an eternal principle of gratitude, covenant loyalty, and compassion, not merely a ceremonial law.   Persembahan perpuluhan merupakan praktik yang telah lama diperdebatkan di kalangan orang Kristen, terutama mengenai relevansi dan makna teologisnya dalam Perjanjian Lama. Banyak orang Kristen memberi perpuluhan tanpa memahami sepenuhnya dasar Alkitab dan makna rohani di baliknya. Penelitian ini bertujuan untuk menggali makna teologis persembahan perpuluhan dalam Perjanjian Lama serta implikasinya bagi kehidupan Kristen masa kini. Penelitian menggunakan metode kajian pustaka kualitatif dengan menganalisis teks-teks Alkitab (Kejadian, Imamat, Bilangan, Ulangan, Maleakhi) serta karya-karya ilmiah yang relevan tentang perpuluhan. Hasil penelitian mengungkapkan empat makna teologis utama: (1) perpuluhan sebagai ucapan syukur atas apa yang dimiliki; (2) menahan perpuluhan menyatakan perlawanan terhadap Tuhan; (3) perpuluhan sebagai pengakuan kedaulatan Tuhan atas segala milik; dan (4) perpuluhan bernilai kekal yang berakar pada iman, perjanjian, dan belas kasihan kepada orang miskin. Penelitian ini menyimpulkan bahwa perpuluhan bukan sekadar kewajiban hukum, tetapi suatu disiplin rohani yang mencerminkan hubungan seseorang dengan Tuhan dan komitmen terhadap keadilan sosial. Kontribusi: Penelitian ini memberikan kontribusi berupa kerangka teologis yang komprehensif tentang makna perpuluhan dalam Perjanjian Lama, dengan menegaskan bahwa perpuluhan adalah prinsip abadi tentang ucapan syukur, kesetiaan perjanjian, dan belas kasihan, bukan sekadar hukum seremonial.